Character education development strategy based on Islamic religious education at Muhammadiyah Jakarta Junior High School - Suhardin, Suhardin; Erwina, Erwina; Samudi, Samudi (Al-Liqo: Jurnal Pendidikan Islam, 2025)
Character education is a system that instills character values in students including knowledge, awareness, determination and willingness and action to realize the values of goodness towards God, self, fellow human beings, the environment and nationality. Meanwhile, to obtain good character education for educators, it must be based on Islamic religious education. Islamic religious education is a planned effort in preparing students to recognize, understand, appreciate and believe in and respect adherents of other religions. The purpose of this study is to examine and analyze the strategy of developing character education based on Islamic religious education. This research uses a qualitative method of phenomenology type, with data collection through observation, interviews and documentation and analysis using data reduction, data display model and conclusion drawing. The results of the research findings are: The development of character education based on Islamic religious education, including: morning roll call activities, reciting the pledge of tawhid and loyalty to Islam, reading verses of the Qur'an and praying, fostering students based on regulations and standard operating procedures, fostering students' concern for others, fostering organizations, students' interests and talents, fostering love for the environment and exemplary by educators. The most basic finding of this research is the change and commitment of Muhammadiyah Jakarta Junior High School students to carry out worship and have good character in carrying out the learning process at school.